Impact of Long-Acting Somatostatin Analogues on Glucose Metabolism in Acromegaly: A Hospital-Based Study. (26th April 2018) - Shen, Ming; Wang, Meng; He, Wenqiang; He, Min; Qiao, Nidan; Ma, Zengyi; Ye, Zhao; Zhang, Qilin; Zhang, Yichao; Yang, Yeping; Cai, Yanjiao; ABuDuoReYiMu, Yakupujiang; et al.
Abstract : Purpose. To evaluate the change in glucose tolerance in treatment-naïve patients with acromegaly after administration of SSA and to identify predictive factors of glucose impairment during SSA therapy. Methods. Oral glucose tolerance testing (OGTT) was performed on 64 newly diagnosed and treatment-naïve patients with acromegaly both at pretreatment and 3 months after initiation of treatment with long-acting SSA. Insulin resistance (IR) was assessed by homeostatic model assessment- (HOMA-) IR and ISOGTT . Insulin secretion was assessed by HOMA- β, INS0 /BG0, IGI (insulinogenic index), IGI/IR, ISSI2, and AUCINS /AUCBG . Receiver-operating characteristic (ROC) curves were generated to determine the optimal cutoffs to predict the impact of SSA on glucose metabolism. Results. Pretreatment, 19, 24, and 21 patients were categorized as having normal glucose tolerance (NGT), impaired glucose tolerance (IGT), and diabetes mellitus (DM), respectively. Posttreatment, IR, represented by ISOGTT, was significantly improved in all 3 groups. Insulin secretion, represented by HOMA- β, declined in the NGT and IGT groups, but was unaltered in the DM group. The glucose tolerance status deteriorated in 18 (28.1%) patients, including 13 patients in the NGT group and 5 patients in the IGT group. Deterioration was associated with lower baseline BG120 (plasma glucose 120 min post-OGTT), less reduction of growth hormone (GH), and greater reduction of insulin secretion after SSA therapy. BG120 greater than 8.1 mmol/l provided the greatest sensitivity and specificity in predicting the stabilization and/or improvement of glucose tolerance status after SSA treatment (PPV 90.7%, NPV 66.7%, p < 0.001 ). Conclusions. The deterioration of glucose metabolism induced by SSA treatment is caused by the less reduction of GH and the more inhibition of insulin secretion, which can be predicted by the baseline BG120 during OGTT.